RiceRBP: A Resource for Experimentally Identified RNA Binding Proteins in Oryza sativa - Doroshenk, Kelly A.; Crofts, Andrew J.; Morris, Robert T.; Wyrick, John J.; Okita, Tom W. (Frontiers in Plant Science, 2012)
RNA binding proteins (RBPs) play an important role not only in nuclear gene expression, but also in cytosolic events, including RNA transport, localization, translation and stability. Although over 200 RBPs are predicted from the Arabidopsis genome alone, relatively little is known about these proteins in plants as many exhibit no homology to known RBPs in other eukaryotes. Furthermore, RBPs likely have low expression levels making them difficult to identify and study. As part of our continuing efforts to understand plant cytosolic gene expression and the factors involved, we employed a combination of affinity chromatography and proteomic techniques to enrich for low abundance RBPs in developing rice seed. Our results have been compiled into RiceRBP (http://www.bioinformatics2.wsu.edu/RiceRBP), a database that contains 257 experimentally identified proteins, many of which have not previously been predicted to be RBPs. For each of the identified proteins, RiceRBP provides information on transcript and protein sequence, predicted protein domains, details of the experimental identification and whether antibodies have been generated for public use. In addition, tools are available to analyze expression patterns for the identified genes, view phylogentic relationships and search for orthologous proteins. RiceRBP is a valuable tool for the community in the study of plant RBPs.